Silver Nanoparticles Synthesis with Kersen Leaf Extract (Muntingia calabura L.) as a Reductor and Its Application for Hydrogen Peroxide Detection - Rizqi, Puji; Alauhdin, Mohammad (Indonesian Journal of Chemical Science, 2021)
Silver nanoparticles (NPP) have been developed and applied for various purposes, including to detect glucose levels in the blood. Glucose levels can be determined indirectly by measuring H2O2 levels using a colorimetric method. Therefore, it is necessary to develop a colorimetric method that is sensitive to H2O2. The purpose of this study was to obtain NPP which has a high sensitivity to H2O2. The NPP synthesis was carried out by reducing AgNO3 using Kersen leaf extract (Muntingia calabura L.) with Polyvinyl alcohol (PVA) as a stabilizer. The results showed that the volume ratio of AgNO3 0,1 mM and the extract of 60: 1 was the optimum condition for the synthesis. UV-Vis spectra showed a maximum absorbance peak at a wavelength of 411-415 nm and only experienced a small shift in the absorbance peak after 15 days. Characterization using the Particle Size Analyzer (PSA) showed that the particles have a size distribution of 170.9 nm. The sensitivity test of NPP towards H2O2 concluded that NPP was able to detect H2O2 up to a concentration of 0.229 mM with a linearity range of 0,001 to 50 mM.